Towards a framework for a resilient supply chain in a turbulent environment: a review of its drivers. (2017) - Lakhal, Salem Y.
In recent years, unexpected events such as natural disasters, including earthquakes and tsunamis, as well as revolutions and acts of vandalism have become frequent. Events such as these can break down the supply chain flow. The supply chain's capacity to recover quickly and to re-establish its flow is characterised by the supply chain's resilience. The resilient supply chain receives significant attention from managers and researchers operating in the supply chain field. This study focuses on developing a framework for a resilient supply chain in a turbulent environment when it is faced with unexpected events. For this purpose, the four supply chain drivers - inventory, transportation, facilities, and information - will be exploited. This framework will be used to reinforce the supply chain resilience and to minimise the negative impact of unexpected events thereby favouring a quick return to business. This work contributes to our understanding of supply chain dynamics in a turbulent environment.